EFEKTIVITAS PENERAPAN METODE HIKARI DALAM MENINGKATKAN KETERAMPILAN MEMBACA ARAB GUNDUL DAN ARAB BERHAROKAT SISWA KELAS XI MAN 2 KEBUMEN TAHUN AJARAN 2016/2017 - Fikri, Wahyu Ngainul; Hasyim, Mohamad Yusuf Ahmad; Qutni, Darul (Program studi Pendidikan Bahasa Arab UNNES, 2018)
Reading skills are the ability to recognize and understand the content of something written by pronouncing or digesting it in the heart. Reading bald is a process of communication between readers with the author through the Arabic text without a written essay, then directly in it, there is a cognitive relationship between a spoken language with written language. Based on preliminary observations in MAN 2 Kebumen made the researchers are still many students who have not read Arabic bald and not fluent reading Arabic amateur. Therefore, researchers offer Hikari method to solve the problem in school. The type and design of this research is quantitative and quasi-experimental with randomized pretest-posttest control group design. A technique of collecting data using test and non-test. The test instruments used were questionnaires, interviews, documentation and observation.The value experimental class of the post-test grade average score of Arab skeletal reading skill and Arab bald reading comprehension skill is 89.20 and 82,06 from the previous pre-test score of 68.86 and 67,58. The value control class of the post-test average score of Arab skeletal reading skill and Arab bald reading comprehension skill is 80.51 and 74,48 from the previous pre-test average score of 67.41 and 66,72. Abstrak ___________________________________________________________________ Keterampilan membaca adalah kemampuan mengenali dan memahami isi sesuatu yang tertulis dengan melafalkan atau mencernanya didalam hati. Membaca Arab gundul adalah proses komunikasi antara pembaca dengan penulis melalui teks arab tanpa harakat yang ditulisnya, maka secara langsung didalamnya ada hubungan kognitif antara bahasa lisan dengan bahasa tulis. Berdasarkan observasi awal di MAN 2 Kebumen yang dilakukan peneliti masih banyak siswa yang belum bisa membaca Arab gundul dan belum lancar membaca Arab berharokat. Oleh karena itu, peneliti menawarkan metode Hikari untuk mengatasi masalah tersebut disekolah.Teknik pengumpulan data menggunakan tes dan non-tes. Instrumen tes yang digunakan adalah angket, wawancara, dokumentasi dan observasi.Besarnya nilai rata-rata post-test kelas eksperimen keterampilan membaca Arab gundul dan Arab berharokat adalah 89,20 dan 82,06 dari nilai rata-rata pre-test yang sebelumnya adalah 68,86 dan 67,58. Sedangkan besarnya nilai rata-rata post-test kelas kontrol keterampilan membaca Arab gundul dan Arab berharokat adalah 80,51 dan 74,48 dari nilai rata-rata pre-test yang sebelumnya adalah 67,41 dan 66,72.